Measures and incentives for enhancing the competitiveness of sectors with export potential in developing countries: evidence and lessons from experience (UNCTAD New YorkUS, 1992)
Highlights briefly the importance of resource availability in building competitive export supply capabilities and the role of government intervention in the development of national productive bases. Examines the trade policy experiences of a few selected developing countries. Analyses the experience of developing countries with exchange-rate management, export incentives, sectoral targeting, export processing zones, and import liberalization.
DC